Sulawesi Bird Report - Paul Andrew; Derek A Holmes (KUKILA, 1990)
All notable records of Sulawesi birds collected by various observers over the period from 1976 to 1990 are summarized in a single compilation, in a format that will become standard for each of Indonesia's seven faunal regions.